Race, insurance type, and stage of presentation among lung cancer patients - Robbins, Anthony; Lerro, Catherine; Barr, Ronald (My University, 2014)
BACKGROUND: The percentage of adolescent and young adult (AYA) patients with cancer (those aged 15-39 years) diagnosed at a distant stage of disease did not significantly change between 1975 and 2004. It has been hypothesized that a lack of health insurance may be a significant risk factor for a diagnosis of distant-stage disease among AYA patients, but to the authors’ knowledge this has not been examined in a national sample. METHODS: The National Cancer Data Base, a hospital-based cancer registry, was used to obtain data regarding incident cancer cases among patients aged 15 years to 39 years who were diagnosed between 2004 and 2010. After all exclusions, a total of 285,448 cases were available for analysis; all AYA cancer sites were included. A retrospective study was conducted to assess the association between insurance status and stage of disease at diagnosis. RESULTS: After adjusting for age, race/ethnicity, facility type, ZIP code-based income and education levels, and US Census region, it was found that among males, uninsured patients were 1.51 times more likely to be diagnosed at a distant stage of disease compared with patients with private insurance (95% confidence interval, 1.46-1.55). Among females, the effect of insurance was stronger, with uninsured patients found to be 1.86 times more likely to be diagnosed at a distant stage (95% confidence interval, 1.79-1.94). The effect of insurance status was substantially stronger for malignancies that are more amenable to early detection (melanoma, thyroid carcinoma, breast carcinoma, genitourinary carcinoma), and substantially weaker for those that are less amenable to early detection (lung carcinoma, adrenocortical carcinoma, Wilms tumor). CONCLUSIONS: In a large national sample of AYA patients with cancer, insurance status was found to be a strong independent risk factor for distant-stage disease at the time of diagnosis.
Keywords: adolescents, young adults, health insurance, cancer disparities, health care reform